Mineralogical study of Sediment samples of Kachua, Chandpur district for investigation of arsenic bearing minerals (Journal of Bangladesh Academy of Sciences, 2009)
Sixteen sediment samples of different depth (up to 122 m) were studied by X-ray diffraction (XRD) method. The samples were collected from a test borehole, which was drilled by Bangladesh Water Development Board (BWDB) at Kachua, Chandpur district. All the samples were characterized and different minerals have been identified in the samples. Quartz is the major mineral and was found to be in the range of 54.97 - 97.88 %. Two arsenic bearing minerals namely, iron arsenate, Fe2As(AsO4)3 and arsenic selenide telluride, AsSe0.5Te2 were found in the samples of depth 55.20 m and 100.60 m, respectively. Bangladesh Atomic Energy Commission (BAEC) in collaboration with the United States Geological Survey (USGS) conducted the groundwater sampling campaign for shallow and deep tubewells in Kachua upazila. From the hydro-chemical results, the concentrations of arsenic in shallow tubewells were found above the maximum permissible limit (50 ppb). Concomitantly, the mineralogical study of sediment samples in the same area reflects that the shallow aquifers of Kachua upazila are contaminated by arsenic due to the presence of arsenic bearing minerals. doi: 10.3329/jbas.v32i1.2436 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 1-12, 2008